Soybean Imports and the Construction of Global Dependence in Indonesia's Food System - Febrianto; Novayanti Sopia Rukmana (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
Indonesia's dependence on soybean imports, which accounts for 70–75% of national demand, cannot be understood solely as a technical failure of agriculture, but rather as a social construct resulting from an unequal global political economy. This article analyzes how the discourse of development, trade liberalization since the 1990s, and the dominance of multinational corporate oligopolies have institutionalized dependence as a “practical inevitability” that normalizes Indonesia's subordination in the global food system. Unlike the technocratic approach that dominated previous literature, this study integrates a constructivist perspective with new dependency theory to unravel the asymmetrical power relations hidden behind narratives of comparative efficiency and market integration. The main novelty lies in proving that food dependency is not the result of rational economic calculations, but rather a discursive product reinforced by state policies, the WTO trade regime, and corporate control over the global value chain. Findings show that domestic policies biased towards rice, the absence of producer price protection, and permissive imports create a self-reinforcing cycle of dependency. The transformation towards food sovereignty requires breaking the structure of dependency through agrarian reform, strengthening local production, and repositioning the paradigm from global market integration towards development based on food sovereignty.